Mindful with your baby for mothers of infants with (parental) stress in a non-clinical setting: a wait-list controlled pilot trial - Eva Sophie Potharst; Irena Veringa-Skiba; Esther van Broekhuizen; Susan Maria Bögels (BMC, 2022)
Abstract Background Because of the far-reaching negative consequences of high levels of (parental) stress for the mother, infant, the mother-infant relationship, and family functioning, psychological support for young mothers is important. Mindful with Your Baby is a mindfulness-based intervention, originally developed and evaluated in a clinical population of mothers with mental health issues and/or babies with regulation problems. The current pilot examines whether Mindful with Your Baby for mothers with symptoms of (parental) stress offered in a non-clinical setting is also effective and acceptable. Methods In this pilot waitlist-controlled trial, 17 mothers with infants (2-15 months) admitted themselves for a Mindful with Your Baby training in a non-clinical setting because of (parental) stress. Mindful with Your Baby was offered in groups of three to six mother-infant dyads and consisted of eight weekly 2-h sessions. Participants completed questionnaires on symptoms of parental stress, general stress, depression, anxiety, mindfulness and self-compassion at 8-week waitlist, pretest, posttest and 8-week follow-up. Results There were no training drop-outs, attendance rate was 92.5%, and the training was evaluated positively: all mothers (100%) felt they got something of lasting importance as a result of taking the training, and reported becoming more conscious as a parent, and 93% reported changing their lifestyle or parenting as a result of the training. Multilevel analyses showed no significant changes between waitlist and pretest. At posttest, a significant improvement occurred in all outcome measures compared to pretest, of moderate to large effect sizes. At follow-up, a significant improvement was seen compared to pretest in all outcomes except anxiety compared to pretest, of small to moderate effect sizes. Conclusions Mindful with Your Baby appears an acceptable and effective intervention for mothers with a baby who experience (parental) stress but who have not been referred to specialized mental health care. A low threshold access to Mindful with Your Baby in non-clinical settings could provide a timely and positive interference in (parental) stress.